CircRNAs: Roles in regulating head and neck squamous cell carcinoma - Han, Xiao; Tian, Ruxian; Wang, Cai; Li, Yumei; Song, Xicheng (Frontiers in Oncology, 2022)
Head and neck squamous cell carcinoma (HNSCC), the most common head and neck malignant tumor, is characterized by single treatment method, poor prognosis, and low 5-year survival rate. Due to the lack of therapeutic targets, there is a serious shortage of targeted drugs. Therefore, exploring the regulation mechanism of HNSCC and identifying effective therapeutic targets will be beneficial for the treatment of HNSCC. Circular RNA (CircRNA) is a class of RNA molecules with a circular structure, which is widely expressed in the human body. CircRNAs regulate gene expression by exerting the function of the miRNA sponge, thereby mediating the occurrence and development of HNSCC cell proliferation, apoptosis, migration, invasion, and other processes. In addition, circRNAs are also involved in the regulation of tumor sensitivity to chemical drugs and other biological functions. In this review, we systematically listed the functions of circRNAs and explored the regulatory mechanisms of circRNAs in HNSCC from the aspects of tumor growth, cell death, angiogenesis, tumor invasion and metastasis, tumor stem cell regulation, tumor drug resistance, immune escape, and tumor microenvironment. It will help us discover new diagnostic markers and therapeutic targets, and provide new ideas for the diagnosis and treatment of HNSCC.